Increasing Referrals of Patients With Gastrointestinal Cancer to a Cancer Rehabilitation Program: A Quality Improvement Initiative. Issue 4 (April 2021) - Nadler, Michelle B.; Rose, April A.N.; Prince, Rebecca; Eng, Lawson; Lott, Anthony; Grant, Robert C.; Jones, Jennifer M.; Enright, Katherine
Abstract : BACKGROUND: People with cancer are at risk for initial, late, and long-term effects of cancer and its treatments. Cancer rehabilitation (CR) focuses on prevention/treatment of these sequelae and optimization of physical, social, and vocational functioning. Our center has a multidisciplinary impairment-driven outpatient CR program, but referrals of patients with GI cancer were low. AIMS: We aimed (for 2019, relative to 2018) (1) to increase CR referrals of patients with GI cancer by 50% and (2) to increase the proportion of referrals coming from oncologists. Balancing measures included inappropriate referrals and cancellations. METHODS: A rapid cycle improvement approach was used to optimize GI referrals to the CR program. Barriers to CR referral were identified through a literature review and informal interviews of GI clinicians. Barriers included (a) knowledge of CR program existence, (b) awareness of the referral process, (c) time, and (d) lack of CR program exposure. The team used Plan-Do-Study-Act (PDSA) cycles every 2 months from January to December 2019 to address barriers. A p-chart was used to analyze the results. RESULTS: PDSA cycles included CR program advertisement, a presentation to GI staff, nurse-led patient identification, patient-facing posters, and clinician thank-you emails. The p-chart showed a 100% relative increase in referral numbers and an improvement in the percentage of patients referred by oncologists from 51% to 75%. There was no significant change in inappropriate referrals or cancellations. CONCLUSION: Through PDSA cycles, we improved the total number of patients with GI cancer and percentage referred by an oncologist to a CR program. Future work will assess sustainability.